Od współpracy miast do współpracy akademickiej – przykład Państwowego Uniwersytetu im. Pawła Tyczyny w Humaniu i Uniwersytetu im. Adama Mickiewicza w Poznaniu (Instytut Kultury Europejskiej UAM) - Jędraszczyk, Katarzyna; Krywoszeja, Igor (Studia Europaea Gnesnensia, 2021)
The article describes various aspects of academic cooperation between two universities: the Pav- lo Tychyna Uman State Pedagogical University (Ukraine) and the Adam Mickiewicz University in Poznań (Poland), especially the AMU Institute of European Culture in Gniezno (formerly the Euro- pean College, Adam Mickiewicz University). The description of the scientific, cultural and teaching activities of both centers suggests a model of cooperation built on the basis of regular grassroots activity.